Temporal and Spatial Variation of Geographical Population Distribution in Jordan for the Period (1994 – 2015) Using GIS - Khawaldeh, Bashar; Abu-Sabha, Kayed (Dirasat: Human and Social Sciences, 2022)
The study aimed at analysing temporal and spatial patterns of population distribution in Jordan at governorate level. It also aimed to define the influencing geographical factors that affected the population distribution and caused the changes over the last decades based on census data of 1994, 2004, and 2015 years. Several approaches and statistical methods were used in this study to achieve study objectives, including analytical and descriptive, evolutionary, and spatial analysis approaches along with some quantitative methods. The choropleth maps and population density maps were created for mapping the population distribution in Jordan. In addition, the researchers has defined and the future population projections at governorate level in Jordan. The study revealed that there is a population concentration during the study period in three main Jordanian governorates: Amman, Irbid and Zarqa. Population numbers are also predicted to increase in some governorates in the future. The study concluded that both natural and human factors have influenced population distribution in Jordan, and the impact of the latter factors are more significant. Accordingly, the study showed that there are three main factors affecting the geographical distribution of population in Jordan: population growth, political and economic conditions in neighbouring Arab countries, and the reclassifying bases of urban areas in Jordan. The study recommends the need for population strategies and policies to be applied to face the changes that occur to population distribution in Jordan. Population densities among governorates and its influencing factors and consequences should be taken into consideration when planning for regional development.